KEPASTIAN HUKUM DAN PERLINDUNGAN HUKUM HAK ATAS TANAH - Hadisiswati, Indri (Ahkam: Jurnal Hukum Islam, 2014)
Giving ownership of land is intended to guarantee rights ofpeople legally. As an implementation of UUPA, the governmentregisters the ownership of land in Indonesia as stated in chapter19 UUPA. Technically, the basis for registering land is statedin Peraturan Pemerintah Number 10/1961 about land registerwhich is renewed in Peraturan Pemerintah No 24/1997.Kata kunci: Kepastian Hukum, Perlindungan Hukum, Hakatas Tanah